(3ehLR JGQjN GdMQhH GdUdjHjI aj GdeTQb GdESdGej hTQbj MhV GdeJhSW (B/s - (3ZQhSjg, Qjfjg,s 1885-1952; (3EjHT, CMeOs; (3ZQhSjg, Qjfjg,s 1885-1952. ((3CHh XHj, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3gjFI CHh XHj ddSjGMI hGdKbGaI (B((3GdeLeY GdKbGaj(B)(3, EUOGQGJ OGQ GdcJH GdhWfjs, 2014)
(3JQLY CgejI GdMQhH GdUdjHjI Edi CfgG JTcd JLQHI aQjOI aj JGQjN GdYQhHI hGdESdGe, gPg GdJLQHI djSJ HMGd ef GdCMhGd ef GdJLGQH GdYGHQI GdeMOhOI GdCKQ hGdfJGFL, Hd gj JLQHI cHQi edjFI HGdOQhS, jfHZj dfG Cf fJOGQSgG hfHMKgG aj cd hbJ(B. (3ef GdhGVM Cf GdChVGY GdJj JMjW HGdYGde GdYQHj hGdESdGej Gdjhe JLYdfG fTYQ HCffG aj hVY CbQH eG jchf Edi GdhVY GdPj YGT ajg CSdGafG efP JSYI bQhf eVJ, GdCeQ GdPj jJWdH efG OQGSI JGQjN gPg GdMQhH GdUdjHjI OQGSI YdejI hGajI(B. (3aj gPG GdcJGH ef JCdja YVh GdCcGOjejI GdaQfSjI GdeDQN GdcHjQ Qfjg ZQhSjg, fbQC deMI ehLRI EfeG hGajI Yf JGQjN gPg GdMedGJ GdJj OGeJ (B193 (3YGeG ; OhGaYgG, hbGFYgG, hBKGQgG GdGLJeGYjI hGdKbGajI, hGdedGMX aj gPG GdcJGH EfUGa GdeDQN dMVGQJfG GdYQHjI GdESdGejI(B. s
Keywords: (3GdMQhH GdUdjHjIs -- (3GdHdGO GdESdGejIs -- (3JGQjNs